¿Cómo fortalecer la comunidad en la vialidad rural? Necesidades de formación y capacitación a partir de las voces comunitarias. Experiencias con comunidades del cantón de Naranjo, Costa Rica - Pérez-Carrillo, Yolanda (2022)
This article seeks to establish the relationship between continuing education and the education and training processes received by the communities of the canton of Naranjo, from the point of view of community leaders who are part of the Community Development Associations and the Roads Committee. These communities participate in a research - extension projectconducted by the School of Sociology of the National University. The methodology was qualitative, using participative techniques such as community workshops, in conjunction with the use of oral sources. It is from their experiences and stories that they give meanings to the training needs required by the communities. These training processes, through continuingeducation, empower the knowledge capacities of the members of the local organizations, thus allowing the opening and strengthening of community participative venues, not only in their actions, but also in decision-making.